2023
DOI: 10.1021/acsomega.2c07681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metal Contamination in Soil Samples around Rampal, Bangladesh

Abstract: Rising soil pollution has recently emerged as a significant global issue as a result of increased industrialization, urbanization, and inadequate waste management. In Rampal Upazila, soil contamination with heavy metals resulted in a significant deterioration of quality of life and life expectancy, so the study's goal is to appraise the level of heavy metal contamination in soil samples. Inductively coupled plasma−optical emission spectrometry was used to identify 13 heavy metals (Al, Na, Cr, Co, Cu, Fe, Mg, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 78 publications
3
7
1
Order By: Relevance
“…This study's findings corroborate the outcomes published by Abdullah et al (2019), where they reported the metal concentrations to be elevated and recorded above the permissible limits suggested by the WHO [24]. Parvez and colleagues (2023) documented the elevated levels of Al, Co, Fe, and Pb in soil samples [17]. Meanwhile, the most substantial average levels in various soil categories for Ca, Mg, K, Na, and Mn were identified by Khan and Shah in 2023 [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study's findings corroborate the outcomes published by Abdullah et al (2019), where they reported the metal concentrations to be elevated and recorded above the permissible limits suggested by the WHO [24]. Parvez and colleagues (2023) documented the elevated levels of Al, Co, Fe, and Pb in soil samples [17]. Meanwhile, the most substantial average levels in various soil categories for Ca, Mg, K, Na, and Mn were identified by Khan and Shah in 2023 [25].…”
Section: Discussionsupporting
confidence: 91%
“…A notable positive statistically significant correlation was observed between Fe, Mg, Al, and K, while Fe correlated statistically significantly negatively with Ca concentration. A robust association among the detected metallic elements suggests their shared provenance within the studied area, with their alignments influenced by similar determining factors [17]. Conversely, a significant negative correlation was found between calcium (Ca) and Al, Na, Mg, and K. These data indicate that these elements originated from a shared source throughout the study area.…”
Section: Pearson Correlation Matrixmentioning
confidence: 72%
“…These concentrations were found to be higher when compared to the investigation by (Abdullahi et al, 2016) (soil from the vicinity of a kaolin milling plant); (Chanda and Gupta.,2021) (soil from an industrial area of Gida) whose Zn concentrations were in the range 0.42 to 6.37 mg/kg and 0.52 to 4.00 mg/kg respectively. This could be attributed to anthropogenic activities, atmospheric depositions and urbanization (Abdullahi et al, 2016;Govil et al, 2001;Parvez et al, 2023). However, the concentrations of Zn derived from this research were found to be lesser when compared to investigation by (Tüzen, 2003) for heavy metals in soils collected at Tokat, Turkey, near high-density traffic and textile plant roads whose concentrations were 60±5 and 74±6 (mg/kg) respectively.…”
Section: Resultscontrasting
confidence: 54%
“…It was also recorded that Zn concentrations in soils collected at the vicinity of an Aluminium plant in Tajikistan, Slovakia, and Hungary; separate farmlands located in the western part of Nasarawa State, Nigeria was in the range 34.14 to 89.25 mg/kg and 10.51 to 27.40 mg/kg (Mohammad et al, 2023;Rasulov et al, 2020) were comparable to the Zn concentrations in this study. The findings by (Wei et al, 2011) and (Parvez et al, 2023) revealed that Zn concentrations in soils collected from the vicinity of a mining area located in China and Rampal Power Station in Bangladesh were higher and in the range 42.3 to 148.4 mg/kg and 6.7 to 74.6 mg/kg respectively. The investigation carried out by (Magaji et al, 2020) revealed similar characteristics for the concentration of Zn.…”
Section: Resultsmentioning
confidence: 98%
“…Water and soil contamination has always been a noticeable matter in environmental studies, leading to the developing and designing heavy metal ions receptors [ [1] , [2] , [3] , [4] ]. Mercury is a highly toxic metal [ [5] , [6] , [7] ] and its compounds are used in various industries and present in wastewaters, which can accumulate in living organisms.…”
Section: Introductionmentioning
confidence: 99%